2021
DOI: 10.5295/cdg.201320ak
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of the Factors Influencing Social Entrepreneurship: A Gendered Approach

Abstract: Purpose: This study examines how entrepreneurial ecosystem factors (entrepreneurial finance, entrepreneurial education, physical and commercial infrastructure, culture, and R&D transfer activities) shape social entrepreneurial activities (SEA) of men and women. Design/methodology/approach: Panel data from 35 countries are examined through General Methods of Moments (GMM) with Arellano Bond tests for the period of ten years (2005-2014). Findings: Our results indicate that women are more likely to get involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 76 publications
(95 reference statements)
0
4
1
Order By: Relevance
“…Commercial and professional infrastructure, such as lawyers, technology consultants, accountants, suppliers, and subcontractors, does not impact entrepreneurial activity, contrary to the results of Khursheed et al [98], which indicate that commercial infrastructure has a positive impact on social entrepreneurship. Professionals like lawyers and accountants help with the challenges that entrepreneurs face in their journey to create a new business [78,79].…”
Section: Latin America Determinants Of Entrepreneurial Activitiescontrasting
confidence: 80%
See 1 more Smart Citation
“…Commercial and professional infrastructure, such as lawyers, technology consultants, accountants, suppliers, and subcontractors, does not impact entrepreneurial activity, contrary to the results of Khursheed et al [98], which indicate that commercial infrastructure has a positive impact on social entrepreneurship. Professionals like lawyers and accountants help with the challenges that entrepreneurs face in their journey to create a new business [78,79].…”
Section: Latin America Determinants Of Entrepreneurial Activitiescontrasting
confidence: 80%
“…The second element that significantly fosters entrepreneurial activity is commercial and professional infrastructure. Khursheed et al [98] found similar results in social entrepreneurship activity. Physical infrastructure in the Middle East has a significant negative impact on entrepreneurship activity, contrary to the results of Yan and Guan [99] and Guerrero et al [54], which indicate that physical infrastructure increases the entrepreneurial activity.…”
Section: Middle East Determinants Of Entrepreneurial Activitiesmentioning
confidence: 63%
“…Therefore, finding finance is a huge challenge for an entrepreneur, particularly, women entrepreneurs face severe challenges than male entrepreneurs in terms of lack of access to finance, cultural restrictions on mobility and lack of spouse support (Memon, 2020). For the progress of an economy, women’s participation and empowerment are recognized as a significant tool and to achieve this objective, entrepreneurship is known as the most suitable option (Muhammad et al , 2020; Khursheed et al , 2021). In developing countries, women entrepreneurs usually need small loans for launching their startup while banks are reluctant to provide a loan without any security (Rashid and Ratten, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The probability of enhanced performance is substantially more arduous for a women entrepreneur, who has to face and overcome business difficulties besides the complications associated with operating a business in a male governed business environment (Mustafa et al, 2021;Al-Shami et al, 2019;Selvadurai, 2019;Aliyu et al, 2019;Alam et al, 2011). Still, many women have chosen to run their businesses on their own (Khursheed et al, 2021;Muhammad et al, 2020;Hisrich & Brush, 1984). Additionally, women entrepreneurs have been traumatized by the shock of the Covid-19 pandemic and have had constraints accessing financial capital, which affected their business performance (Chipfunde et al, 2021;Welsh et al, 2018) Furthermore, (Dy & Jayawarna, 2020;Seetharaman, 2020;Werner, 2020;Bartik et al, 2020) elucidated that the Covid-19 pandemic has affected the micro-enterprises of all entrepreneurs as well as women entrepreneurs tremendously.…”
Section: Research Problem Statementmentioning
confidence: 99%